Governance in Regional-Based Small and Medium Enterpris (SME) Empowerment for Economic Growth in Metro City - Putra, M. Reza Andrea; Pitriani Nuryana, Risma (Universitas Indonesia Mandiri, 2026)
The purpose of this study is to analyze the economic potential of each region in Metro City and formulate development strategies to improve the regional economy from a public administration perspective. The research method uses a descriptive-analytical qualitative approach with secondary data from BPS, RPJMD, and SME/IKM profiles. The findings reveal the unique characteristics of each sub-district: Metro Pusat as a trade center, Metro Utara with its ecoprint batik center, and the spread of creative SMEs/IKMs such as tapis weaving and handicrafts throughout the region. Supported by a high Human Development Index/HDI (70.18 in 2020), Metro City has a strong human resource foundation, but it is not yet supported by an integrated regional development strategy. Policy recommendations focus on implementing the fourth mission of the RPJMD through three strategies: (1) developing economic clusters based on regional uniqueness, (2) improving infrastructure support and technology access for SMEs/IKMs, and (3) strengthening triple helix collaboration between the government, private sector, and academia. The conclusion emphasizes that optimizing regional potential through a strategic public administration approach will drive inclusive and sustainable economic growth in Metro City.